Análise das condições de lubrificação de motores testados em dinamômetro a frio utilizando dados tribológicos obtidos em laboratório - Tonella Junior, Jorge Luiz (2020)
This research presents a comparative case study between two different tribosystems of piston ring, cylinder liner and lubricants. It was studied two engine blocks BR10 model, given by Renault of Brazil. For such affair, it was proposed a methodology of tribological data use, obtained through laboratory tests, more specifically on a reciprocating tribometer, with contact similar to piston ring-cylinder liner to determine friction coefficients. It was used MatLab® software to calculate the lubricant film thickness corresponding to equivalents to diverse engine rotations on cold dynamometer test. The cylinder liners and piston rings were characterized for its microstructure and roughness, which were considered as steady condition for the case studies. Empirical solutions are presented to determine a relation between friction coefficient and engine rotations during dynamometer test, having as variable the lubricant oil viscosity. It was concluded that the methodology used for laboratory correlation and test equipment was strong enough to predict the friction variations expected with relation of viscosity, engine rotation and temperature through a Stribecklike curve behavior.